Retirement Choice in a Frictionless Labor Market (2019)
ABSTRACT: This paper investigates optimal consumption and retirement choices in an environment without labor market frictions but in which agents face liquidity constraints. To this end, we characterize the optimal savings strategy and the threshold level of assets associated with the decision to retire or not, which in turn yield the optimal consumption and work choices. In line with the literature, we show that wealth plays a crucial role since it determines whether or not it is optimal to save and then to retire. However, our results differ from the conventional view as we find that, for those workers with low levels of assets, retirement is never optimal regardless of income uncertainty.